Assessment of White Matter Tract Damage in Patients with Amyotrophic Lateral Sclerosis: A Diffusion Tensor MR Imaging Tractography Study - Agosta, F.; Pagani, E.; Petrolini, M.; Caputo, D.; Perini, M.; Prelle, A.; Salvi, F.; Filippi, M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Most DTI studies in ALS have been limited to the assessment of the CST damage. In this study, we used DTI tractography to investigate whether microstructural abnormalities occur in the major motor and extramotor WM tracts in mildly disabled patients with ALS. MATERIALS AND METHODS: Brain conventional MR imaging and DTI were performed in 24 patients with probable or definite ALS and mild disability (ALSFRS score, ≥20) and 20 healthy controls. The mean disease progression rate was 0.62 (range = 0.08–2.50). DTI tractography was used to segment the CST, the corpus callosum, and the major WM association tracts (ie, cingulum, uncinate fasciculus, inferior fronto-occipital, inferior longitudinal, and superior longitudinal fasciculi). RESULTS: Compared with healthy controls, patients with ALS showed significantly decreased FA and significantly increased MD and radial D of the CST bilaterally (P values from .005 to .01). Patients with ALS also had a significantly increased axial D of the right uncinate fasciculus relative to controls (P = .04). CST FA significantly correlated with the rate of disease progression (right CST: r = −0.50, P = .02; left CST: r = −0.41, P = .05). CONCLUSIONS: Patients with ALS and mild disability have preferential damage to the CST. The association of CST damage with the rate of disease progression suggests that DTI has the potential to provide in vivo markers of ALS evolution. The subtle involvement of the uncinate fasciculus may precede the appearance of behavioral symptoms in patients with ALS. ALSamyotrophic lateral sclerosisALSFRSALS Functional Rating Scaleaxial Daxial diffusivityCSTcorticospinal tractDEdual-echoDTIdiffusion tensor imagingFAfractional anisotropyFTDfrontotemporal dementiaMDmean diffusivityradial Dradial diffusivityWMwhite matter